Pharmacological Treatment of Depression in Alzheimer’s Disease: A Challenging Task - Cassano, Tommaso; Calcagnini, Silvio; Carbone, Antonio; Bukke, Vidyasagar Naik; Orkisz, Stanislaw; Villani, Rosanna; Romano, Adele; Avolio, Carlo; Gaetani, Silvana (Frontiers in Pharmacology, 2019)
Besides the memory impairment, Alzheimer’s disease (AD) is often complicated by neuropsychiatric symptoms, also know as behavioral and psychological symptoms of dementia, which occur in one-third of patients at an early stage of the disease. Although the relationship between depressive disorders and AD is debated, remain still unresolved the question if depression is a prodromal symptom preceding impending cognitive deficits or an independent risk factor for dementia. Moreover, there is growing evidence in the literature that conventional antidepressants have not been found to be effective in depression associated with AD and, therefore, there is an urgent need to understand the neurobiological mechanism underlying the resistance to the antidepressants. Another important question that remains to be addressed is whether the antidepressant treatment is able to modulate the levels of amyloid-β peptide (Aβ), which is a key pathological hallmark in AD. Therefore, the present review summarizes the present knowledge of the relationship between depression and AD and focused on the resistance of antidepressant therapies in dementia. Finally, we have briefly outlined the preclinical and clinical evidence regarding the probable mechanisms by which antidepressants modulate Aβ pathology. To our opinion, understanding the cellular processes that regulate Aβ levels may provide greater insight into the disease pathogenesis and might be helpful in designing novel selective and effective therapy against depression in AD.